Dystopian Depths in John Lanchester’s The Wall (2019) - Jarrar, Sana' (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study argues that John Lanchester's The Wall (2019) is a dystopian novel as it incorporates all the elements of dystopian fiction. The elements of dystopian fiction detected in the novel include environmental ruin, technological predomination, inequality, enslavement, violence, despotism, and the propaganda used to mislead the citizens of society. From the perspective of post -colonialism, the Anthropocene, and Marxism, this study follows a descriptive qualitative approach. These theories help to uncover various dimensions of the text, with Marxism shedding light on class conflict and exploitation, Post-colonialism exposing the oppression and discrimination against the “Others,” and the Anthropocene theory highlighting the impact of human activities on the environment. The purpose of the study is to satirize the status que including the environmental, political, and social aspects. The study argues that The Wall exceeds being a pessimistic narrative; it is a channel for contemplation, consideration, satire, and transformation. Overall, the study thoroughly addresses these dimensions by analyzing the novel and how it portrays a dystopian world that reflects contemporary fears related to oppression, despotism, and environmental as well as technological degradation. The particular significance of this study lies in being a useful vehicle to learn about global challenges. In terms of the findings, the study warns about how current challenges could cause havoc if left uncurbed. Serving as both a mirroring and a thrust for transformation, the study holds a far-reaching implication in the sphere of change.